QUALITY EXCALATION OF LOCAL SALT - Arini Mutiarahmi, Siva
Indonesia is a maritime country with a coastline of 99,000 kilometers. The vast ocean area makes Indonesia has abundant marine and fishery potential. One of the marine and fisheries sectors that needs to be developed is salt production, considering that salt has quite a lot of benefits, both for daily consumption and for industrial needs. But unfortunately, salt production in Indonesia is still not able to fulfil the existing needs, so that Indonesia still imports a lot of salt. In addition, local salt still cannot meet the specifications of industrial salt because of its low purity and a lot of impurities. Therefore, it is necessary to develop technology for a better salt refining process. In this study, the salt purification process will be carried out by the hydroextraction method. The purpose of this research is to obtain salt with high purity to meet industrial salt specifications. In this study, common salt will be brought into contact with a brine solution. The varied conditions in this experiment include the ratio of salt to brine solution (F:S) and contact time. The tested F:S ratios are 1:45, 1:50, and 1:55, while the contact times used are 45 minutes, 50 minutes, 55 minutes, 65 minutes, and 75 minutes. The salt obtained from hydroextraction is then tested to determine the NaCl content using argentometric titration. Based on the experimental results, the highest NaCl content obtained is 99.19%, which occurs when the F:S ratio is 1:55 with a contact time of 55 minutes.